AB0014 A MIR146A POLYMORPHISM IS ASSOCIATED WITH ANTI-CARP ANTIBODIES IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Perricone, Carlo; Ciccacci, Cinzia; Ceccarelli, Fulvia; Leccese, Ilaria; Mettola, Giuseppe; Rufini, Sara; Alessandri, Cristiano; Spinelli, Francesca; Politi, Cristina; Latini, Andrea; Novelli, Giuseppe; Valesini, Guido; et al.
Abstract : Background: (SLE) is a chronic autoimmune disease with a complex pathogenesis in which genes and environmental factors interact leading to a protean clinical picture. Joint involvement is one of the most common manifestations in SLE patients, with a prevalence ranging from 69 to 95%. This feature significantly influences the patients' quality of life, possibly leading to disability and impaired functional performance in daily activities. Identification of prognostic biomarkers, able to identify patients at risk to develop this more aggressive phenotype, is mandatory. Autoantibodies associated with inflammatory arthritis, such as Rheumatoid Arthritis (RA), have been shown to play a role also in SLE arthritis. For instance, ACPA can be found in approximately 16% of SLE patients and, recently, it was demonstrated that anti-carbamylated proteins antibodies (anti-CarP) can be identified in up to 28.3% of SLE patients (1). Objectives: Thus, our aim was to analyze previously identified loci associated with SLE in a cohort of SLE patients to evaluate their influence on autoantibody production. Methods: We recruited 52 Italian SLE patients. A panel of 34 SNPs in 19 genes involved in immune response, autophagy and inflammation, was selected. SNPs genotyping was performed by allelic discrimination assay by TaqMan assays (Applied Biosystems, Foster City, CA, USA) and ABI PRISM 7000. The main clinical/laboratory features (including injury index and disease activity) were collected on an electronic platform. The presence of Rheumatoid Factor (RF), ACPA, and anti-CarP antibodies was investigated. All autoantibody assays were carried out in duplicate, commercial enzyme-linked immunosorbent assay (ELISA) kits were used and the results were evaluated according to the manufacturers' instructions. Detailed methods are described in (1). A genotype/phenotype correlation analysis was performed. Results: Clinical and demographic data of patients are described in table 1 . The variant allele of rs2910164 (MIR146a) (P=0.03) was significantly associated with presence of anti-CarP antibodies in SLE. Specifically, patients carrying the C allele of MIR146a were more likely to have anti-CarP antibodies (P=0.01, OR 5.018, 95% CI 1.414-17.811). Among the clinical and laboratory features, the same polymorphism was associated with presence of arthritis in clinical history (P=0.02), and with anti-dsDNA positivity (P=0.025). In a multinomial logistic regression analysis, MIR146A was independently associated with anti-CarP (P=0.017, Exp(B)=5.433, 95%CI 1.345-21.944). Conclusion: Carbamylation is a non-enzymatic process consisting in the addition of a cyanate group on self-proteins determining a modification in the tertiary structure. This change causes the generation of new epitopes and the consequent production of autoantibodies. This is the first report suggesting that anti-CarP production is genetically driven. Indeed, Mir146a expression is altered in SLE and has been linked with autoantibody production in lupus-prone mice models. Probably, the higher IFNa levels observed in patients carrying the C allele can be responsible for such higher autoantibody production. Reference: [1] Massaro L, et al. Anti-carbamylated protein antibodies in systemic lupus erythematosus patients with articular involvement. Lupus. 2018;27:105-111. Disclosure of Interests: Carlo Perricone Speakers bureau: BMS; Lilly, Celgene, Sanofi, Cinzia Ciccacci: None declared, Fulvia Ceccarelli: None declared, Ilaria Leccese: None declared, Giuseppe Mettola: None declared, Sara Rufini: None declared, cristiano alessandri: None declared, francesca spinelli: None declared, Cristina Politi: None declared, Andrea Latini: None declared, Giuseppe Novelli: None declared, Guido Valesini: None declared, Paola Borgiani: None declared, fabrizio conti: None declared